2015
DOI: 10.17224/energagric.2015v30n3p217-224
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade Do Corte Dos Rebolos Na Colheita Mecanizada Da Cana-De-Açúcar Em Diferentes Condições Operacionais

Abstract: RESUMO:O comprimento dos rebolos colhidos por colhedoras de cana-de-açúcar picada influenciam diretamente a qualidade da matéria-prima colhida, pois pode diminuir a deterioração, a presença de impurezas, as perdas e o custo com transportes. Ajustado dentro da cabine do operador, o comprimento dos rebolos varia de acordo com a configuração de ajuste dos componentes do sistema de alimentação das máquinas como os rolos alimentadores e o rolo picador, bem como o número de facões presentes neste. O objetivo foi ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…With these results, it is possible to observe that for the plant losses, the variable speed has greater influence, as described by Ramos et al (2014), where an increased working speed of the harvester resulted in increased losses of raw material. Similarly, Segato et al (2011), when verifying the influence of increasing the sugarcane harvester's speed on plant losses, concluded that there is a relationship between these factors.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…With these results, it is possible to observe that for the plant losses, the variable speed has greater influence, as described by Ramos et al (2014), where an increased working speed of the harvester resulted in increased losses of raw material. Similarly, Segato et al (2011), when verifying the influence of increasing the sugarcane harvester's speed on plant losses, concluded that there is a relationship between these factors.…”
Section: Resultsmentioning
confidence: 67%
“…Notwithstanding, Ramos et al (2014), evaluating the quality of mechanized sugarcane harvesting, describes that the vegetable impurities were not influenced when there was a change in the working speed or in the rotation of the harvester's motor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mechanical harvesting of sugarcane, improper regulation of the harvester according to crop conditions, especially of its cleaning equipment, can increase the content of vegetal and mineral materials and, consequently, leading to losses of raw material (RAMOS et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…O sistema de colheita mecanizada da cana-de-açúcar foi desenvolvido a partir da necessidade de se realizar a colheita com maior capacidade operacional, melhorando a logística do corte e do carregamento e sua compatibilização com o ritmo da indústria ( VOLTARELLI et al, 2014;RAMOS et al, 2015). Esse sistema tem sido constantemente discutido em vários aspectos, no que diz respeito às modificações necessárias para que haja melhoria na adequação entre as máquinas existentes no mercado e as particularidades dos canaviais de cada uma das unidades produtoras ( VOLTARELLI et al, 2014).…”
Section: Introductionunclassified